FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KUALITAS PELAYANAN KESEHATAN DI RSU MITRA MEDIKA AMPLAS MEDAN TAHUN 2021 - Elmina Tampubolon; Novrika Silalahi; Muhraza Siddiq (Jurnal Penelitian Kesmasy, 2021)
Factors Associated with the Quality of Public Health Services at Mitra Medika Amplas General Hospital Medan in 2021. Thesis, Department of Public Health, Faculty of Public Health, Deli Husada Delitua Health Institute. This study aims to analyze the relationship of tangible, reliability, responsiveness, assurance, empathy with the quality of health services at RSU Mitra Medika Amplas Medan. The population of this study were patients at Mitra Medika Amplas Hospital, Medan. In the sample can be 99 respondents. The sampling technique used in this research is purposive sampling. The method used in this study was analyzed by Chi-Square test. The results of the research on tangible variables in the good category reached 79.3%. The reliability variable obtained 80.3%. The responsiveness variable was obtained 78.5%. Assurance variable obtained 80.5%. Empathy variable obtained 78.9%. So it can be concluded that there is a relationship between tangible, reliability, responsiveness, assurance, empathy variables with the quality of health services at Mitra Medika Amplas Medan General Hospital in 2021.